Silver nanoparticles enhance the efficacy of aminoglycosides against antibiotic-resistant bacteria - Dove, Autumn S.; Dzurny, Dominika I.; Dees, Wren R.; Qin, Nan; Nunez Rodriguez, Carmen C.; Alt, Lauren A.; Ellward, Garrett L.; Best, Jacob A.; Rudawski, Nicholas G.; Fujii, Kotaro; Czyż, Daniel M. (Frontiers in Microbiology, 2023)
As the threat of antimicrobial-resistant bacteria compromises the safety and efficacy of modern healthcare practices, the search for effective treatments is more urgent than ever. For centuries, silver (Ag) has been known to have antibacterial properties and over the past two decades, Ag-based nanoparticles have gained traction as potential antimicrobials. The antibacterial efficacy of Ag varies with structure, size, and concentration. In the present study, we examined Ag nanoparticles (AgNPs) for their antimicrobial activity and safety. We compared different commercially-available AgNPs against gram-negative Escherichia coli, Pseudomonas aeruginosa, Acinetobacter baumannii, and gram-positive Staphylococcus aureus methicillin-resistant and susceptible strains. The most effective formula of AgNPs tested had single-digit (µg/mL) minimum inhibitory concentrations against gram-negative multidrug-resistant clinical bacterial isolates with novel and emerging mechanisms of resistance. The mode of killing was assessed in E. coli and was found to be bactericidal, which is consistent with previous studies using other AgNP formulations. We evaluated cytotoxicity by measuring physiological readouts using the Caenorhabditis elegans model and found that motility was affected, but not the lifespan. Furthermore, we found that at their antibacterial concentrations, AgNPs were non-cytotoxic to any of the mammalian cell lines tested, including macrophages, stem cells, and epithelial cells. More interestingly, our experiments revealed synergy with clinically relevant antibiotics. We found that a non-toxic and non-effective concentration of AgNPs reduced the minimum inhibitory concentrations of aminoglycoside by approximately 22-fold. Because both aminoglycosides and Ag are known to target the bacterial ribosome, we tested whether Ag could also target eukaryotic ribosomes. We measured the rate of mistranslation at bactericidal concentration and found no effect, indicating that AgNPs are not proteotoxic to the host at the tested concentrations. Collectively, our results suggest that AgNPs could have a promising clinical application as a potential stand-alone therapy or antibiotic adjuvants.